ANALYSIS OF FACTORS AFFECTING AUDITOR SWITCHING (CASE STUDY ON MANUFACTURING COMPANIES LISTED ON THE MALAYSIA EXCHANGE FOR THE PERIOD OF 2019 AND 2020) - Rizka Fitri Nuraini; Icih Icih (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
The purpose of this study is to determine the effect of audit quality, firm size, and audit fees on auditor switching in manufacturing companies listed on the Malaysian Stock Exchange. The analysis used in this study is logistic regression analysis with a sampling technique that is purposive sampling. With this technique, 92 samples were obtained with audit quality results having a significant effect on auditor switching, while firm size and audit fee variables had no significant effect on auditor switching.